THE ABRI CASSEROLE (DORDOGNE, FRANCE): REASSESSING THE 14C CHRONOLOGY OF A KEY UPPER PALEOLITHIC SEQUENCE IN SOUTHWESTERN FRANCE. Issue 5 (9th October 2020) - Ducasse, Sylvain; Pétillon, Jean-Marc; Aubry, Thierry; Chauvière, François-Xavier; Castel, Jean-Christophe; Detrain, Luc; Langlais, Mathieu; Morala, André; Banks, William E; Lenoble, Arnaud
ABSTRACT: Discovered at the beginning of the twentieth century, the Abri Casserole (Dordogne, France) was the subject of salvage excavations in the early nineties. The fieldwork revealed a sequence of 13 archaeological levels that document human occupations from the Gravettian to the Magdalenian, including very rare and poorly known assemblages (e.g. Early Badegoulian, Protosolutrean) that afford a particular importance to this sequence. Results of a previous dating program that focused on the Badegoulian levels were obtained in 1994 but were neither extensively published nor discussed. Five AMS 14 C ages obtained for the Gravettian and Solutrean assemblages in the early 2010s served to complement the site's chronology. However, since the beta counting ages for the Badegoulian levels were in conflict with the accepted AMS chronology for the region's late Pleniglacial archaeological record, a new AMS dating program was implemented to renew the radiometric framework of this specific portion of the sequence. Compared to the previous beta counting measurements, the seven newly obtained AMS ages are about 1000 years older (23.3–20.5 cal ka BP) and congruent with other AMS-dated Badegoulian sequences. These results thereby restore the inter-site chronological coherence of the Solutrean–Badegoulian and Badegoulian–Magdalenian transitions.